Rearing Copepods for Mosquito Control - Jorge Rey; Sheila O'Connell (EDIS, 2004)
Copepods are tiny aquatic crustaceans (shrimp, crabs lobster, and relatives) that are widespread in both fresh and salt water habitats. They are voracious predators of mosquito larvae and as such, can be used to control mosquito production from water holding areas. Copepod cultures are relatively easy to maintain, but getting the cultures started requires some effort and time. Also, some equipment that may not be readily available to the average home owner (such as a dissecting microscope) can make life a lot easier. This document is ENY-697, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date February, 2004.